2007
DOI: 10.1021/tx700023z
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantitation of Acrolein-Derived 1,N2-Propanodeoxyguanosine Adducts in Human Lung by Liquid Chromatography-Electrospray Ionization-Tandem Mass Spectrometry

Abstract: Acrolein, a widely distributed environmental pollutant, reacts with dGuo in DNA to form two pairs of 1,N2-propano-dGuo adducts: (6R/S)-3-(2'-deoxyribos-1'-yl)-5,6,7,8-tetrahydro-6-hydroxypyrimido[1,2-a]purine-10(3H)one (alpha-OH-Acr-dGuo) and (8R/S)-3-(2'-deoxyribos-1'-yl)-5,6,7,8-tetrahydro-8-hydroxypyrimido[1,2-a]purine-10(3H)one (gamma-OH-Acr-dGuo). alpha-OH-Acr-dGuo is more mutagenic and mainly induces G --> T transversions. A recent study demonstrated that acrolein-DNA adducts are preferentially formed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
166
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(176 citation statements)
references
References 22 publications
7
166
2
1
Order By: Relevance
“…[36][37][38] Enal adducts are lower oxidation state homologues of 21 and the notion that acrolein, crotonaldehyde, and 4-HNE undergo similar chemistry was confirmed by the observation that γ-OH-PdG (9) ring-opens to the N 2 -(3-oxopropyl)-dG aldehyde (1) when placed opposite dC. 39 We further hypothesized that these aldehydes react with other nucleobases in the complementary DNA strand, forming interstrand cross-links, which exist as equilibrium mixtures of carbinolamine (17), imine (18), or pyrimidopurinone (19) species. The aldehyde in structure 1 also yields peptide-and protein-DNA conjugates (20); 40,41 however, analysis of this literature is beyond the scope of this Account.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…[36][37][38] Enal adducts are lower oxidation state homologues of 21 and the notion that acrolein, crotonaldehyde, and 4-HNE undergo similar chemistry was confirmed by the observation that γ-OH-PdG (9) ring-opens to the N 2 -(3-oxopropyl)-dG aldehyde (1) when placed opposite dC. 39 We further hypothesized that these aldehydes react with other nucleobases in the complementary DNA strand, forming interstrand cross-links, which exist as equilibrium mixtures of carbinolamine (17), imine (18), or pyrimidopurinone (19) species. The aldehyde in structure 1 also yields peptide-and protein-DNA conjugates (20); 40,41 however, analysis of this literature is beyond the scope of this Account.…”
Section: Introductionmentioning
confidence: 85%
“…17,[66][67][68] Since they equilibrate with non-cross-linked species, and require the presence of the 5′-CpG-3′ sequence, they may be present at low levels in tissue samples. Nevertheless, it has been reported that acrolein preferentially binds at 5′-CpG-3′ sites, a consequence of cytosine methylation at these sequences.…”
Section: Potential Biological Significancementioning
confidence: 99%
See 3 more Smart Citations